2021
DOI: 10.1002/nafm.10548
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Active and Passive Larval Sampling Gears in Monitoring Reproduction of Invasive Bigheaded Carps in Large‐River Tributaries

Abstract: Silver Carp Hypophthalmichthys molitrix and Bighead Carp H. nobilis, collectively known as bigheaded carps (BHC), are invasive fishes in the Mississippi River and surrounding basins. Increasing evidence suggests harmful impacts of BHC on native fisheries (e.g., competition). Monitoring the abundance of BHC is difficult with traditional fisheries gears, and few studies have evaluated early life stage sampling. Identifying the spawning locations of BHC through early life stage sampling has the ability to enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Larval fishes in these habitats are likely younger and passively drifting with the current (Holland, 1986), potentially making them easier to capture. Alternatively, larval bigheaded carp can migrate out of the main channel to areas with lower velocity at 5 to 6 days of age and larger, more developed larvae that are better swimmers may be more likely to avoid the ichthyoplankton net (Chapman and George, 2011;Roth et al, 2023). In contrast to detection, occupancy of carp and freshwater drum was similar among habitats, suggesting that all habitats are used by larval carp and drum.…”
Section: Discussionmentioning
confidence: 99%
“…Larval fishes in these habitats are likely younger and passively drifting with the current (Holland, 1986), potentially making them easier to capture. Alternatively, larval bigheaded carp can migrate out of the main channel to areas with lower velocity at 5 to 6 days of age and larger, more developed larvae that are better swimmers may be more likely to avoid the ichthyoplankton net (Chapman and George, 2011;Roth et al, 2023). In contrast to detection, occupancy of carp and freshwater drum was similar among habitats, suggesting that all habitats are used by larval carp and drum.…”
Section: Discussionmentioning
confidence: 99%
“…Other ichthyoplankton surveys have also noted an advantage of light traps for detecting invasive gobies, which lack a planktonic stage (Tucker et al, 2019). By contrast, invasive carp, primarily passive dispersers at early life stages, are more effectively captured using net‐based methods (Roth et al, 2021). Strategically timed sampling exploiting the unique ecological, physiological or sensory aspects of invasive species at different early life stages (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Egg count estimates for Silver Carp ranged between 233,739 and 2,510,504 with an average of1,484,695. Many age-0 fishes are difficult to detect in large river systems(Brewer and Ellersieck 2011), including Bighead and Silver Carp(Roth et al 2020). Carp are extremely difficult to sample(Wanner and Klumb 2009;Bouska et al 2017;Roth et al 2020) and detection was reported at approximately 38% in the presumably highly populated Illinois River basin(Coulter et al 2018).…”
mentioning
confidence: 99%